Mathematics of Finance / Business Mathematics (Book). - Cannon, Arthur M.; Allison, Charles W. (The Accounting Review, 1952)
Reviews two books. "Mathematics of Finance," by Albert E. May; "Business Mathematics," by Walter F. Cassidy and C. Carl Robusto.